Smartphone and tablet use pattern in children up to 5 years old in Spain: a cross-sectional study - Sonia de Paz-Cantos; Adrián González-Marrón; Cristina Lidón-Moyano; Maria Cerrato-Lara; Ana Díez-Izquierdo; Jose M Martínez-Sánchez (Revista Latino-Americana de Enfermagem)
Objective: to characterize the smartphones and tablets use pattern in a sample of children up to 5 years old and assess with which variables it is associated. Method: cross-sectional study of 410 parents of children up to 5 years of age. Data were obtained from an online questionnaire. Questions about the time and pattern of daily use of smartphones and tablets were collected. We calculated the overall percentage (and 95% confidence interval) and median (and interquartile range) of each device’s use time and according to the variables associated with the child, and the respondent’s characteristics. Results: an estimated 44.7% (95% CI: 37; 51) of children used both smartphones and/or tablets daily. The median use time for smartphones and tablets separately was 30 minutes per day for smartphones (8.6-38.6) and 30 (17.1- 60.0) for tablet. In children who have free access to the devices, 11.6% (95% CI: 6; 16) use these devices up to 30 minutes after waking up on weekdays, 15.4% (95% CI: 10; 21) during weekends and 14.0% (95% CI: 8; 19) use smartphone and/or tablet up to 1 hour before going to bed. Conclusion: more than 4 out of 10 children in our sample used smartphones and/or tablets daily. Community nursing may be a viable avenue for implementing educational programs focused on promoting healthy practices in children’s electronic device usage given the pattern of excessive screen use in the pediatric population.